Modeling of steam permeation through the high temperature proton-Conducting ceramic membranes - Song, F.; Zhuang, S.; Tan, X.; Liu, Shaomin (John Wiley & Sons, Inc., 2019)
The BaCeO3-based perovskite oxide can be applied as a steam-permeable membrane due to their noticeable mixed oxygen ion and proton conducting properties. In this article, a transient model of the steam permeation through the BaCe0.9Y0.1O3-d perovskite membrane at elevated temperatures has been developed with the Poisson–Nernst–Planck equations for analyzing the steam permeation process, in which the distribution of charged defects in the membrane is carefully considered. The effects of the operating temperature, the membrane thickness, the steam partial pressure, and the electric potential difference between two membrane sides during the steam permeation have been simulated and discussed. The modeling results indicate there exists a maximum value of the spontaneous electric potential difference with the temperature rise and the external electric potential can obviously increase the steam flux. The model is validated using the experimental results from literature under steady state operational conditions. © 2018 American Institute of Chemical Engineers AIChE J, 65: 777–782, 2019.